(untitled) (Fiep Bulletin - online, 2011)
To identify the profile of educators in age, sex, education, time in daycare and in current institution; know the professional pathway, the reason for career choice and the educators function; learn about the proposed activities of educators and their conception about Neuropsicomotor Normal Development (DNPMN); identify the interest of educators in continuing education and discuss the possibility of phisioterapist action in educational areas. The sample was about 24 educators of 0 to 6 years old children of the Child Educational Center’s Pioneers in Balneario Camboriu city. Was applied an individual semi-structured interview using a voice recorder, which basically consisted of 14 questions of personal identification and the conception of the educators about child DNPMN. For the results analysis was used the Bardin scale. All the educators were female, mean age 30 years and 10 of them still with incomplete higher education. Was found educators uncertainty about their professional identity and function. For most, the career choice was made by a hasten to teach. There was educators uncertainty about their DNPMN conception, do not understand in which stage the children are, do not able to identify delays in DNPMN and do not offer activities for children emphasizing the DNPMN. With this result we observed a lack of information from educators about the DNPMN and, therefore, is expected to continue the study to be possible the inclusion process of the physiotherapy in daycares to sucefully empower the educators.